2013
DOI: 10.1002/adsc.201200929
|View full text |Cite
|
Sign up to set email alerts
|

A Deacetylation–Diazotation–Coupling Sequence: Palladium‐ Catalyzed CC Bond Formation with Acetanilides as Formal Leaving Groups

Abstract: Acetanilides can be deacetylated and diazotized in situ, and subsequently used in Pd-catalyzed coupling reactions without isolation of the diazonium intermediate. Heck reactions, Suzuki crosscoupling reactions, and a Pd-catalyzed [2 + 2 + 1] cycloaddition have been investigated as terminating C À C bond-forming steps of this one-flask sequence. The sequence does not require the exchange of solvents or removal of by-products between the individual steps, but proceeds by addition of reagents and catalysts in due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 93 publications
1
15
0
Order By: Relevance
“…In general, our model also shows a higher incidence rate to the southern hemisphere compared to the northern hemisphere (Figure 10d), which is associated with the northward offset in the planet's magnetic dipole. Furthermore, ground-based and MESSENGER observations both showed a north-south asymmetry in the antisunward Na tail with an excess in the northern tail (e.g., Baumgardner et al, 2008;McClintock et al, 2008;Potter & Killen, 2008;Vervack et al, 2010;Schmidt, 2013). Using a Monte Carlo simulation, Schmidt (2013) showed that the main source of Na in the northern tail is in fact the Na from the southern hemisphere that drifts to the opposite hemisphere of the tail as they are pushed antisunward by radiation pressure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, our model also shows a higher incidence rate to the southern hemisphere compared to the northern hemisphere (Figure 10d), which is associated with the northward offset in the planet's magnetic dipole. Furthermore, ground-based and MESSENGER observations both showed a north-south asymmetry in the antisunward Na tail with an excess in the northern tail (e.g., Baumgardner et al, 2008;McClintock et al, 2008;Potter & Killen, 2008;Vervack et al, 2010;Schmidt, 2013). Using a Monte Carlo simulation, Schmidt (2013) showed that the main source of Na in the northern tail is in fact the Na from the southern hemisphere that drifts to the opposite hemisphere of the tail as they are pushed antisunward by radiation pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the intense solar irradiation at Mercury's surface, which is due to the proximity of Mercury to the Sun, thermal and photon stimulated desorption are suggested to have the largest contribution to the formation of Mercury's neutral exosphere (e.g., Gamborino et al, 2019;Leblanc & Johnson, 2003;McGrath et al, 1986;Mura et al, 2009;Wurz et al, 2010). However, the particles released by these two processes have relatively low velocities and thus are more gravitationally bound to the planet, compared to the particles released by micrometeorite impact vaporization and solar wind ion sputtering (e.g., Leblanc & Johnson, 2003;Schmidt et al, 2010Schmidt et al, , 2012Schmidt, 2013;Wurz et al, 2010). The sputtering process depends on the momentum and energy of the impacting ions as well as the surface composition and sputtering yield (e.g., Killen et al, 2001;Lammer & Bauer, 1997;.…”
Section: 1029/2019ja027706mentioning
confidence: 99%
See 2 more Smart Citations
“…As for (R)-phenylglycol oxidation, in order to recycle the expensive cofactor NAD + , an NAD + regeneration system employing AlaDH with NH 4 Cl as ammonia donor was introduced. [18] The conversion could reach as high as 99 % in glycine/NaOH buffer with pH ranging from 7.5-8.5 within 4 h, replacement of buffer constituent, higher pH or lower NH 4 Cl concentration significantly reduce the conversion (Table S3, supporting information). For transamination, L-Ala was utilized as the amino donor, since the by-product pyruvate can severely inhibit transaminase activity, [19] therefore, in situ removal of pyruvate is very critical not only for keeping the transaminase activity but also for pushing the reaction equilibrium.…”
Section: One Pot Asymmetric Synthesis Of (R)-phenylglycinol From Racementioning
confidence: 98%